2021
DOI: 10.1007/s00401-021-02318-y
|View full text |Cite
|
Sign up to set email alerts
|

Tau immunotherapy is associated with glial responses in FTLD-tau

Abstract: Progressive supranuclear palsy (PSP) and corticobasal degeneration (CBD) are neuropathologic subtypes of frontotemporal lobar degeneration with tau inclusions (FTLD-tau), primary tauopathies in which intracellular tau aggregation contributes to neurodegeneration. Gosuranemab (BIIB092) is a humanized monoclonal antibody that binds to N-terminal tau. While Gosuranemab passive immunotherapy trials for PSP failed to demonstrate clinical benefit, Gosuranemab reduced N-terminal tau in the cerebrospinal fluid of tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…ABBV-8E12 (tilavonemab) and BIIB092 (gosuranemab), which bind tau at the N-terminal side, failed to show efficacy in PSP patients in two phase 2 clinical trials [209,210]. However, decreased CSF free tau and accumulation of tau in lysosomes of emerging perivascular vesicular astrocytes proved that the binding happens as anticipated [209,211]. Reasons for futility in clinical trials include difficulties in earlier diagnosis of PSP, especially preclinical stages, noneffective epitopes and extracellular targeting [210].…”
Section: Tau Immunizationmentioning
confidence: 99%
“…ABBV-8E12 (tilavonemab) and BIIB092 (gosuranemab), which bind tau at the N-terminal side, failed to show efficacy in PSP patients in two phase 2 clinical trials [209,210]. However, decreased CSF free tau and accumulation of tau in lysosomes of emerging perivascular vesicular astrocytes proved that the binding happens as anticipated [209,211]. Reasons for futility in clinical trials include difficulties in earlier diagnosis of PSP, especially preclinical stages, noneffective epitopes and extracellular targeting [210].…”
Section: Tau Immunizationmentioning
confidence: 99%
“…A phase II trial in progressive supranuclear palsy showed that the unbound N-terminal tau in CSF was decreased by 98% in the gosuranemab group and increased by 11% in the placebo group, but the N-terminal tau neutralization does not translate into clinical efficacy (NCT03068468) [ 72 ]. Recently, Kim and his colleagues examined the brain tissues of three individuals receiving gosuranemab and found that gosuranemab treatment may be associated with glial responses including accumulation of tau within astrocytic lysosomes [ 73 ]. However, the phase II study of gosuranemab in participants with early AD was terminated due to the lack of efficacy in slowing cognitive and functional impairment following the placebo-controlled period readout [ 74 ].…”
Section: Immunotherapies Based On Tau Proteinmentioning
confidence: 99%
“…A glial profiling study demonstrated enrichment of astrocytic transcripts in tau-related FTLD degeneration [125]. In humans, tau immunotherapy results have been shown to be associated with glial responses in FTLD-tau [126].…”
Section: Discussionmentioning
confidence: 99%